Aspergillus Terreus-related Ureteral Obstruction in a Diabetic Patient (Iranian Journal of Kidney Diseases, 2013)
An Aspergillus fungal ball is a rare cause of ureteral obstruction attributed to indwelling catheters, stents, antibiotics, anastomotic leaks, obstruction, and immunosuppressive therapy and other immunocompromised states. We describe a case of unilateral ureteral obstruction caused by Aspergillus terreus following ureteroscopic lithotripsy and ureteral stenting in a 45-year-old diabetic man. The patient was successfully treated with endoscopic removal of the fungal mass and oral voriconazole. We also review briefly the clinical features, treatment, and outcome in 9 previously reported diabetic patients with ureteral obstruction due to aspergillosis. Obstructive uropathy related to Aspergillus mass may be suspected in diabetic patients with a history of manipulation, impaired kidney function, and persistent passage of a soft mass in urine. Direct microscopy and culture of multiple urine and ureteral washing are necessary for early diagnosis. Antifungal therapy and endoscopic removal of the mass are needed to reduce morbidity.